Unraveling Indonesia's Diplomacy in the Pacific Region - Pugu, Melyana Ratana (Ridwan Institute, 2024)
This research aims to examine Indonesia's diplomacy in the Pacific Region, specifically during the Joko Widodo administration, focusing on the period spanning the last two decades. Emphasizing the significance of the Pacific Region in Indonesia's current foreign policy, the study employs qualitative research methods, utilizing international relations analysis, to explore diplomatic and cooperative efforts. Data for this study are derived from extensive literature reviews, including journals, books, regulations, and internet sources. The findings indicate that Indonesia, through its